Molar Sound Velocity and Molar Compressibility of Castor Oil at Elevated Temperature and Pressure - Saxena, M.C.; Sircar, Shipra (Asian Journal of Chemistry, 2010)
Molar sound velocity and molar compressibility have been evaluated in castor oil at wide range of temperature and pressure. Their relations with temperature and pressure have been discussed in the light of Rao and Wada Rule.